A single cycle influenza virus coated in H7 haemagglutinin generates neutralizing antibody responses to haemagglutinin and neuraminidase glycoproteins and protection from heterotypic challenge. (4th February 2019) - Powell, Timothy J.; Rijal, Pramila; McEwen-Smith, Rosanna M.; Byun, Haewon; Hardwick, Marc; Schimanski, Lisa M.; Huang, Kuan-Ying A.; Daniels, Rodney S.; Townsend, Alain R. M.
Abstract : A non-replicating form of pseudotyped influenza virus, inactivated by suppression of the haemagglutinin signal sequence (S-FLU), can act as a broadly protective vaccine. S-FLU can infect for a single round only, and induces heterotypic protection predominantly through activation of cross-reactive T cells in the lung. Unlike the licensed live attenuated virus, it cannot reassort a pandemic haemagglutinin (HA) into seasonal influenza. Here we present data on four new forms of S-FLU coated with H7 HAs from either A/Anhui/1/2013, A/Shanghai/1/2013, A/Netherlands/219/2003 or A/New York/107/2003 strains of H7 virus. We show that intranasal vaccination induced a strong local CD8 T cell response and protected against heterosubtypic X31 (H3N2) virus and highly virulent PR8 (H1N1), but not influenza B virus. Intranasal vaccination also induced a strong neutralizing antibody response to the encoded neuraminidase. If given at higher dose in the periphery with intraperitoneal administration, H7 S-FLU induced a specific neutralizing antibody response to H7 HA coating the particle. Polyvalent intraperitoneal vaccination with mixed H7 S-FLU induced a broadly neutralizing antibody response to all four H7 strains. S-FLU is a versatile vaccine candidate that could be rapidly mobilized ahead of a new pandemic threat.